2010
DOI: 10.1038/ng.531
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of hematological and biochemical traits in a Japanese population

Abstract: We report genome-wide association studies for hematological and biochemical traits from approximately 14,700 Japanese individuals. We identified 60 associations for 8 hematological traits and 29 associations for 12 biochemical traits at genome-wide significance levels (P < 5 x 10(-8)). Of these, 46 associations were new to this study and 43 replicated previous reports. We compared these associated loci with those reported in similar GWAS in European populations. When the minor allele frequency was >10% in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
450
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 470 publications
(488 citation statements)
references
References 39 publications
35
450
3
Order By: Relevance
“…The genetic modifier of ALP is reported to have a potential influence on serum ALP activity. 17 Total ALP value is also elevated by some environmental factors, in vitamin D deficiency 2 or in the third trimester of gestation by the increasing placental ALP, which is not affected by TNSALP. 18 Recently, it was shown that patients who are homozygous for the c.1559delT mutation differed in the severity of HPP, including both their symptoms and serum ALP activity.…”
Section: Discussionmentioning
confidence: 97%
“…The genetic modifier of ALP is reported to have a potential influence on serum ALP activity. 17 Total ALP value is also elevated by some environmental factors, in vitamin D deficiency 2 or in the third trimester of gestation by the increasing placental ALP, which is not affected by TNSALP. 18 Recently, it was shown that patients who are homozygous for the c.1559delT mutation differed in the severity of HPP, including both their symptoms and serum ALP activity.…”
Section: Discussionmentioning
confidence: 97%
“…GWAS have suggested a correlation between the TFR2 genomic region and various hematological traits [16][17][18][19]. Recent studies using mouse models of anemia have suggested that loss of Tfr2 in the erythroid compartment could be responsible for either increased RBC counts [21,22,24] or a block in the development of erythroblasts [23].…”
Section: Discussionmentioning
confidence: 99%
“…These observations are suggestive of a relation between TFR2 and erythropoiesis. This concept is also supported by recent genome wide association studies (GWAS) which found an association between TFR2 and various hematological parameters [16][17][18][19]. In one GWAS, an association was found between red blood cell (RBC) number and a SNP centered on the TFR2 gene [16], although the authors did mention that another candidate for this association could be erythropoietin (EPO) [16,18].…”
Section: Introductionmentioning
confidence: 86%
“…b On a given chromosome locus, we tabulated genes separately if they were located in different linkage disequilibrium blocks (see the "Methods" section). c P value is from Ganesh et al 4 d P value is from Kamatani et al 8 e P values were not available. f P value is from Soranzo et al 5 Chromosome 15q22.…”
Section: New Loci Associated With Rbc Traits In Individuals Of Europementioning
confidence: 99%
“…2 The RBC traits have a substantial genetic component, with heritabilities of 0.56, 0.52, and 0.52 reported for RBC count, mean corpuscular volume (MCV), and mean corpuscular hemoglobin (MCH), respectively. 3 Recently, genomewide association studies (GWAS) in cohorts of European ancestry, [4][5][6][7] as well as in a Japanese cohort, 8 have reported multiple quantitative trait loci associated with one or more RBC traits.…”
mentioning
confidence: 99%